Negative magnetic buoyancy and formation of a sunspot belt - Kryvodubskyj, V.N. (Кинематика и физика небесных тел, 2005)
Magnetic buoyancy constrains the magnitude of toroidal field excited by the Ω-effect near the bottom of the solar convection zone (SCZ). Therefore, we examined two negative magnetic buoyancy effects: i) macroscopic turbulent diamagnetism (the γ-effect) and ii) magnetic advection caused by vertical inhomogeneity of plasma density in the SCZ, which we called the ∇ρ-effect. The Sun’s rotation which yields the ∇ρ-effect with new properties was taken into account. The reconstruction of toroidal field was calculated as a result of the balance of mean-field magnetic buoyancy, turbulent diamagnetism and the rotationally modified ∇ρ-effect. It is shown that at high latitudes negative buoyancy effects block the magnetic fields in the deep layers of the SCZ, and this may be the most plausible reason why a deep-seated field here could not become as apparent at the solar surface as sunspots. However, in the region located near equator the ∇ρ-effect causes the upward magnetic advection. So, it can facilitate penetration of strong magnetic fields (about 3000–4000 G) to solar surface where they then arise in the “royal zone” as the sunspots